2010
DOI: 10.1159/000313516
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Topical Application of Virgin Coconut Oil on Skin Components and Antioxidant Status during Dermal Wound Healing in Young Rats

Abstract: Objectives: The present study was undertaken to evaluate the effect of a topical application of virgin coconut oil (VCO) on excision wounds in young rats. Methods: Three sets of experiments with 3 groups of female Sprague-Dawley rats each consisting of 6 animals were used for studying wound closure time, antioxidant status and biochemical parameters. Group 1 was the control; groups 2 and 3 were treated with 0.5 and 1.0 ml VCO, respectively, 24 h after wound creation for 10 days. After the experimental period, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(101 citation statements)
references
References 82 publications
4
82
0
4
Order By: Relevance
“…26 Therefore, utilizing VCO could enhance the efficacy of topical nanoemulsion treatment for the skin of psoriasis patients.…”
mentioning
confidence: 99%
“…26 Therefore, utilizing VCO could enhance the efficacy of topical nanoemulsion treatment for the skin of psoriasis patients.…”
mentioning
confidence: 99%
“…Healing Activity: Nevin et al (2010) reported that VCO-treated wounds healed much faster due to higher collagen and anti-oxidant enzymes activities. It was also observed histopathologically, that there is increase in fibroblast proliferation and nevovascularization in VCO-treated wounds 17 .…”
Section: Anti-microial Activitymentioning
confidence: 99%
“…Three of the identified mechanisms behind these healing effects are its ability to accelerate reepithelialization, improve antioxidant enzyme activity, and stimulate higher collagen crosslinking within the tissue being repaired. 4 In case of allopathic care, the infant may require an appropriate dose of acetaminophen/paracetamol at the time of surgery and again 4 and 8 hours postsurgery.…”
Section: Maxillary Frenectomymentioning
confidence: 99%